The Hayden Kho Jr. sex videos an exploratory study on the public perception about TV star, Maricar Reyes' image before and after the scandal and the implicit role of talent managers in the image formation - Dela Torre, Kathrine Daiane Reyes (2012)
"This research is an exploratory study on how effective public relations is in influencing public perception of local female celebrities involved in sex scandals. College students from the University of the Philippines were used to represent the members of the public and were asked to answer survey questions that would show the effectiveness of public relations in shaping their opinion on a certain female celebrity involved in a sex scandal in a quantifiable manner. From the said sample, two groups were selected to participate in the focus group discussions in order to provide a qualitative understanding and approach to the data gathered understanding and approach to the data gathered from the survey. Using Wilson and Gutierrez'z Constant Reinforcement Theory framed into Geibner's Cultivation theory, this study discovered the effectiveness of mass media in shaping the public's opinion, especially when it involves sensitive issues like the case study, Maricar Reyes' Sex Scandal with Hayden Kho, Jr. This study also discusses the respondents' views about Maricar Reyes' prior to the sex scandal, during the sex scandal and in the aftermath of the sex scandal. It was discovered that some respondents' still perceived Reyes in a negative way even before the controversy. The research confirmed that the audiences are active media consumers who are affected by what media feeds them. The constant reinforcement of a certain idea affects how onw creates opinion on that certain issue."